Vitamin D receptor, interleukin 12B and interleukin 23R gene polymorphisms and risk of chronic plaque psoriasis among patients in a Malaysian hospital - Matnor, Nur Syazana (2017)
Background: Psoriasis is a non-contagious chronic inflammatory disease that primarily affecting the skin and can manifests to joints. The underlying etiology of the disease involves a complex interaction of environment, genetic and immunological factors. Previous studies have reported that inflammatory cytokines are found to be elevated in psoriasis patients. Meanwhile, vitamin D has shown to be an effective treatment for psoriasis but the effectiveness is different between patients. Genetic plays an important role in the pathogenesis of disease and a number of single nucleotide polymorphisms (SNPs) on interleukin 12B (IL12B), interleukin 23R (IL23R) and vitamin D receptor (VDR) genes have been identified. However, the role of these SNPs on the phenotypic expression of psoriasis is still under investigation and none has been done on Malaysian population. Objectives: This study aimed to investigate the association of SNPs of VDR,IL12Band IL23R genes on risk of chronic plaque psoriasis with adjustment for potential confounders such as age, gender, body mass index (BMI), and severity of psoriasis. The interaction between the gene polymorphisms and age of disease onset as well as the severity of the disease on the patients were also assessed. Methods: In this study, a hospital based case control study comprised of 101 chronic plaque psoriasis patients and 99 healthy normal individuals was conducted. Socio-demographic data was recorded for both groups with additional Psoriasis Area Severity Index (PASI) and Dermatology Life Quality Index (DLQI) from psoriasis patients. Extracted DNA was amplified by polymerase chain reaction (PCR) reaction and genotyped for SNP by restriction fragment length polymorphism (RFLP) analysis. Genotype distribution and allelic frequencies were compared between patients and controls. Mean values and odds ratios (ORs) with 95% confidence interval (CI) were calculated using SPSS software (version 19.0) Results: A/C carriers of rs7975232 polymorphism of VDR gene significantly increase the risk of psoriasis (OR 2.049, 95% CI 1.006-4.172, p = 0.048). No significant association reported for polymorphisms of IL12B and IL23R genotypes with risk of psoriasis. C/T carriers of IL23R gene decrease the risk of psoriasis but the result is not significant. Also no significant association reported with gender, race and lifestyle habits including cigarette smoking, alcohol consumption and BMI with risk of psoriasis. Conclusion: Association of rs7975232 polymorphism with chronic plaque psoriasis in Malaysian population shows similarity from previous similar study that had been done in Asian population. This is the first association of selected polymorphisms from various genes conducted in Malaysian population for chronic plaque psoriasis. Such finding might be able to contribute to understand the various responses and resistance to vitamin D therapy in psoriasis and might allow us a step closer in solving the complexity of chronic plaque psoriasis.